MOTIVASI BELAJAR SISWA KELAS XI IPS4 DALAM PEMBELAJARAN SOSIOLOGI DI SMAN I LENGAYANG - RAHMI, ELFIA - (Pendidikan Sosiologi, 2014)
Motivation is impulse that contained in a someone to try to establish behavioral more better meet their needs. For the student the motivation is very important and needed in their school. Without motivation of the learning objectives will be difficult to achieve well. In class XI IPS at SMA 1 Lengayang consist of superior class and distinctions class based on average normal value. This class have several problem such as problem between student and student, student and teacher and they feel gets unfair treatment from their teacher in learning sociology. The condition like this will give impact on studentâs motivation for the student that serious to learn. The problem of this research is how do the studentâs motivation this class in learning sociology at the school. The aim of this research is to describe the motivation of student learning sociology class XI IPS 4 at SMAN 1 Lengayang. This research used qualitatif descriptive approach. The selection techniques is purposive sampling with data collection method were observation, interview and triagulation with data analysis Milles Huberman there are data collection, data reduction, data presentation and drawal/ verication conclusion. Based on the result of the research, the reseacher found that the studentâs motivation in learning sociology at class XI IPS 4 is higher. It will be seen from studentâs intrinsic motivation, Interest, attention, Diligence, an Indenpendence. And studentâs extrinsic motivation, the factor of teacher, the factor of their friends in class, the factor of facilities and infrastructure. Even though they are learn in class that condition often have problem, they take a alternative variety and strategy to achieve good value.